Schooling Process: Is Schooling Experience and Its Outcome the Same for Girls and Boys? - Abdul Wahab Ibrahim; Bashir Ahmad Saleh (Randwick International of Education and Linguistics Science Journal, 2020)
The study examined if schooling experience and teacher’s classroom interaction is the same for senior secondary school adolescent girls and boys in Jigawa state, Nigeria. It also determined whether influence of students’ perceived level of personalisation of the teacher’s classroom behaviour and environment exist on their participation in the classroom learning activities. These were with a view to improving the teacher-student’s relationships and teacher’s classroom effectiveness. The study adopted a survey design. The population consisted of all male and female students in public Senior Secondary Schools in Jigawa state. The sample consisted of 370 Senior Secondary Classes Three (SS III) students. Of this number, 185 were boys and 185 were girls selected through stratified sampling procedure using sex as stratum. Their average age was 15.17 years. A self-developed instrument was used to collect relevant data in the study. Data collected were analysed using Independent t-test statistical method. The results showed that teachers do not significantly interact with girls and boys in the same manner in the classroom. However, there existed a significant influence of students’ perceived level of personalisation of the teacher’s classroom behaviour on their participation in the classroom learning activities. Also, there was a significant influence of students’ perceived level of personalisation of the classroom environment on their participation in the classroom learning activities. It was concluded that schooling experience is not the same for girls and boys respectively. Thus, appropriate interventionist strategies should be put in place to assist realising the objective of equal educational opportunity.